A team approach to applying the International Classification of Functioning, Disability and Health Rehabilitation set in clinical evaluation - Malan Zhang; Yun Zhang; Yun Xiang; Ziling Lin; Wei Shen; Yingmin Wang; Liyin Wang; Jiani Yu; Tiebin Yan (Medical Journals Sweden, 2021)
Objective: To develop a team approach to applying the International Classification of Functioning, Disability and Health Rehabilitation Set (ICF-RS) in clinical evaluation. Design: A Delphi study. Subjects: Experts from rehabilitation institutions in China including physicians, nurses, physiotherapists and occupational therapists. Methods: A 2-round Delphi survey and expert panel discussion were used to generate the team approach. Firstly, the candidate types of professionals for team rating were chosen through expert panel discussion. A carefully selected group of participants was then asked to score the suitability of physicians, nurses, or other candidate therapists for each category's rat-ing, applying the International Classification of Functioning, Disability and Health Rehabilitation Set in clinical evaluation. After initial assignment of cate-gory to types of professionals, a second round Delphi survey was conducted to quantify the professionals' agreement with the category assignments and generate a final team evaluation approach. Results: Thirty of the category assignments achiev-ed consensus. The final team evaluation approach assigned 6 categories to physicians to evaluate, 7 categories to nurses, 9 categories to physiotherapists, and 8 to occupational therapists. Conclusion: Such a team evaluation approach could facilitate implementation of the ICF-RS in clinical settings and provide a more convenient assessment tool for professionals.